Discourse: Leader and the Modern Literature - Ainagul Ussenbekova, Bibizhan Begmanova, Yerkanat Khuatbekuly, Dina Yessenzhan Bibigul Sultanova, (Opción, 2019)
In this article, we show political writings, thoughts andsuggestions by Nazarbayev, his framework of discourse theory viacomparative qualitative research methods. As a result, the poet is also amember of the people. We have stopped on verses to find out,Nazarbayev's policy, communication with the people is how good. Inconclusion, we have witnessed that Nazarbayev's works contain notonly elements of political discourse, but also argumentative, narrative,poetic and discourse.